(untitled) (Desenvolvimento em Questão, 2020)
This study aimed to analyze the ranking of South American companies from the multi-criteria DP2 and VIKOR, considering the creation of value. For this, the information available from companies from four countries (Argentina, Brazil, Chile and Peru) was analyzed, corresponding to a total of 69 companies. In addition, the data referred to the period from 2011 to 2015. It is worth mentioning that in order to measure value creation, the variables EVA and MVA were chosen. In order to elaborate the value creation ranking for EVA, MVA and EVA / MVA, the multicriteria DP2 and VIKOR methods were used. From the results, it can be concluded that the companies of the four South American countries analyzed presented very close positions and, in some cases, were equal in the two analyzed rankings (EVA and MVA). Therefore, the methods were efficient to identify the companies that create the most value in the analyzed countries, which generates more confidence on the part of the investors, who can consider the two variables individually or, analyzed together. Value creation is essential for companies that are looking to leverage more and more. The research becomes relevant since the variables used to carry out this study are essential when it comes to creating value worldwide. In addition, it helps companies choose the best investment options among the companies that have submitted the necessary information, given the wealth presented here through rankings.